DETEKSI Streptococcus Sp PADA Clarias gariepinus MENGGUNAKAN AMPLIFIED ENZYME-LINKED IMMUNOSORBENT ASSAY - Sri P. Astuti Wahyuningsih; R. Warsito; Hastari Wuryastuti; Kamiso H.N. (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1999)
An enzyme-linked immunosorbent assay has been developed which detect Streptococcus sp. Twenty Clarian gariepinus at the age of two weeks was soaked in Streptococcus sp. suspension with concentration of 108 bacteria per ml for two hours. Specimens such as blood, mucous, muscles, heart, kidney, liver, intestines and gill were collected, and assayed for the presence of Steptococcus sp. using ELISA. Result of present study showed that ELISA can be applied to detect an isolated Streptococcus sp. from tissues of Clarias gariepinus. Kidney is a primary target organ (predilection). Therefore, the kidney is a specimen of choice for diagnosis approach (es) of Streptococcus sp. infection.